2001
DOI: 10.1002/jmor.1029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the cuticle in some aquatic oligochaetes (Annelida: Clitellata)

Abstract: An examination of the cuticle of six aquatic oligochaete species using transmission electron microscopy revealed a larger morphological variation than previously known. Three freshwater species, Aulodrilus pluriseta, Spirosperma ferox (both Tubificidae), and Pristina breviseta (Naididae), and three marine species, Clitellio arenarius, Heterochaeta costata (both Tubificidae), and Paranais litoralis (Naididae), were investigated. The arrangement of the collagen fibers in the cuticle differs among the studied spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…A layered epicuticle has been reported for lumbricids (Richards, 1974), for some Brazilian earthworms (Rodriguez Alves et al, 1984), and for several groups of tubificids (Gustavsson and Erséus, 2000;Gustavsson, 2001), and the substructure of the epicuticle has been unique for each studied species. However, in this study, specimens of Heterodrilus paucifascis from different localities deviate in the morphology of the epicuticle.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A layered epicuticle has been reported for lumbricids (Richards, 1974), for some Brazilian earthworms (Rodriguez Alves et al, 1984), and for several groups of tubificids (Gustavsson and Erséus, 2000;Gustavsson, 2001), and the substructure of the epicuticle has been unique for each studied species. However, in this study, specimens of Heterodrilus paucifascis from different localities deviate in the morphology of the epicuticle.…”
Section: Discussionmentioning
confidence: 96%
“…Lack of an orthogonal grid was also reported by Giere (1983) for two tubificids, Thalassodrilus prostatus and Aktedrilus monospermathecus, and by Jamieson (1992) in the naidine Chaetogaster limnaei. The findings by Gustavsson and Erséus (2000) and Gustavsson (2001) show that the Tubificidae encompass a larger variation in the morphology of the cuticle than previously known; these authors concluded that the variation could be associated with phylogenetic relationships. However, thus far the cuticle has only been described at the species level, and the amount of interspecific variation of the morphology of the cuticle is not known.…”
mentioning
confidence: 78%
See 3 more Smart Citations